The Role of Task Complexity And Task Motivation In Language Production - Umi Kalsom, Masrom; Nik Aloesnita, Nik Mohd Alwi; Nor Shidrah, Mat Daud (UKM Press, 2015)
This study investigates the relationship between the cognitive demands of task complexity and learners’ task motivation using task-based instruction during asynchronous computer-mediated communication (ACMC) writing tasks. Eighty-eight participants were assigned with a writing task, each of different complexity level which was manipulated following Robinson Cognition Hypotheses (2001a, 2003, 2005, 2007) along resource-directing (+/- causal reasoning demand) and resource-dispersing (+/- task structure) variables. After the participants have completed the writing tasks, they were asked to complete a questionnaire to gauge their motivation towards the tasks. Further analysis of the data was conducted by using Multivariate Analysis of Variance (MANOVA) and correlational analysis. Analyses of results showed that there is a correlation between task complexity and task motivation among learners. In short, this study is important as it identifies the relationship and roles between task complexity and task motivation in mediating the acquisition of language.